Examining the relationship between e-service recovery quality and e-service recovery satisfaction moderated by perceived justice in the banking context. Issue 6 (22nd June 2020) - Mathew, Sonia; Jose, Ajay; G, Rejikumar; Chacko, Dony Peter
Abstract : Purpose: The study focuses on the core issue faced by bankers on how to retain existing customers who have encountered an e-service failure and who are skeptical about the justice received through the service recovery process. It further endeavors to create an internal bench-marking model for assessing e-service recovery satisfaction. Design/methodology/approach: By the experimental study, the authors confirm a measurement model using structural equation modeling for examining the impact of perceived service recovery quality antecedents on e-service recovery satisfaction moderated by perceived justice. In total, responses from 399 e-banking customers, who had experienced a e-service failure, were recorded using a 5-point Likert scale with a structured questionnaire. Findings: The perceived e-service recovery quality antecedents identified were perceived information quality, digital commitment, perceived employee performance and perceived service orientation of organization. The empirical results revealed that "perceived information quality" was the most significant predictor of e-service recovery satisfaction. Perceived justice moderates the relation between perceived service recovery quality and e-service recovery satisfaction. Research limitations/implications: The research does not contemplate the e-service recovery satisfaction of customers who have undergone multiple service failures. Practical implications: The conclusions of the investigation suggest that the four antecedents of perceived e-service recovery quality model are suitable instruments for creating benchmarks for e-service recovery satisfaction for banks, and that perceived justice moderates the relationship between e-service recovery quality and e-service recovery satisfaction. Therefore, policymakers in banks can use this model to assess the e-service recovery quality, and they ought to enhance the perceived justice feel of the customers who have experienced a service failure. Originality/value: There remains scarcity of empirical research focusing on perceived information quality and digital commitment as antecedents of perceived e-service recovery quality and its effect on e-service recovery satisfaction in the banking context. Furthermore, similar studies within the banking sector have rarely considered perceived justice as a moderator variable. Hence, this paper attempts to accomplish the research gap by empirically testing the e-service recovery satisfaction level of a large sample of the population toward four antecedents of perceived e-service recovery quality rendered by banks and create a benchmark model to ascertain e-service recovery satisfaction.